Understanding How Large Metropolitan/Inner City, Urban Cluster, and Rural Students Perceive Food Systems. Issue 1 (11th January 2018) - Bonnell, Kory J.; Hargiss, Christina L.M.; Norland, Jack E.
Abstract : The purpose of this research was to understand how students in different demographics in the state of Minnesota understand and perceive concepts relating to food systems. Schools within the demographic categories of large metropolitan/inner city, urban cluster, and rural areas were chosen to determine if perceptions and knowledge of students were dependent on the demographic in which they lived. A total of 204 students were surveyed using a variety of types of questions to address research objectives. Results indicate that students have a general understanding of food production and where their food comes from, but as food sources become more complex or items are less common, students become confused. Food access did vary, where rural students used gas stations more than their urban counterparts. Large metropolitan/inner city adolescents had higher occasional use of farmer's market/food stands which can be used as a way to start educational understanding about local foods. Students have a strong willingness to learn more about food systems and other environmental topics in school, but agree that they are not often receiving this interaction in the classroom. All demographics had low interest in local food and gardening, but rural students did have more access to these foods. Implications from this study can help researchers and educators understand students' knowledge and perceptions about the food system, how they influence it, and how this changes across demographics.